Investigation of Dynamic Characteristics of Nomex Composite Sandwich Plate - Şen, Murat; Yıldız, Yunus Onur; Yiğid, Osman; Kara, Sertaç Emre (Sinop University, 2025)
This study investigates the dynamic characteristics of Nomex composite sandwich structures, which are widely utilized in extensive engineering fields such as aerospace, marine, and automotive industries due to their numerous advantages, including high strength, vibration and sound insulation, and thermal resistance. Considering that these structures typically operate under dynamic conditions, understanding their dynamic properties, such as resonance frequencies, vibration modes, and damping ratios, is crucial for their efficient and safe operation. In the presented study, the resonance frequencies, vibration modes, and damping ratios of Nomex composite sandwich plates were determined using the Experimental Modal Analysis (EMA) method. It was observed that the structure exhibited a significant vibration damping ratio at the vibration modes corresponding to its resonance frequencies.

Bu çalışma, yüksek mukavemet, titreşim ve ses yalıtımı ve termal direnç gibi sayısız avantajları nedeniyle havacılık, denizcilik ve otomotiv endüstrileri gibi kapsamlı mühendislik alanlarında yaygın olarak kullanılan Nomex kompozit sandviç yapıların dinamik özelliklerini araştırmaktadır. Bu yapıların genellikle dinamik koşullar altında çalıştığı düşünüldüğünde, rezonans frekansları, titreşim modları ve sönümleme oranları gibi dinamik özelliklerini anlamak, verimli ve güvenli çalışmaları için çok önemlidir. Sunulan çalışmada, Nomex kompozit sandviç plakaların rezonans frekansları, titreşim modları ve sönümleme oranları Deneysel Modal Analiz (EMA) yöntemi kullanılarak belirlenmiştir. Yapının, rezonans frekanslarına karşılık gelen titreşim modlarında önemli bir titreşim sönümleme oranı sergilediği gözlemlenmiştir.
Nomex Kompozit Sandviç Plakanın Dinamik Özelliklerinin İncelenmesi
Keywords: Dynamics; Vibration and Vibration Control; Dinamikler; Titreşim ve Titreşim Kontrolü